The role of Various Factors in the Therapeutic Response of Calcipotriol in Mild to Moderate Plaque Type Psoriasis Patients - Hardyanto Soebono, Siti Aminah Tri Susila Estri Sunardi Radiono (Universitas Gadjah Mada, 2007)
Background: Psoriasis is a chronic skin inflammation and proliferation disease. Natural history of psoriasis depends on the genetic, age, sex, history of treatment and psychosocial stressor. Calcipotriol is suitable for long-term therapy with good efficacy and safety and clinical response variability but its activity is influenced by ultraviolet.Objective: To know the factors that may influence treatment response of calcipotriol ointment on mild to moderate plaque type psoriasis.Method: Longitudinal study of two times daily calcipotriol ointment 0.005% treatment in the psoriasis patients. Factors that may influence the natural course (age, sex, history of psoriasis in family, history of therapy, MED, working location and psychological stressor) were identified. Evaluation of therapy was performed in the 8th weeks and based on the PASI and PDI. Correlation between treatment responses with various factors were analyzed by using student t-test, Pearson and Spearman correlations and multiple linear regression.Result: At the end of study, PASI was shown to decrease 38.45%, while PDI was 28.70% (p